2021
DOI: 10.3390/jof8010011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Multiplex Real-Time PCR DermaGenius® Assay for the Detection of Dermatophytes in Hair Samples from Senegal

Abstract: For the successful treatment of dermatophytoses, especially tinea capitis, there is a need for accurate and rapid diagnostic methods. A lot of recent literature has focused on the detection of dermatophytes directly on sample material such as nails, hair and skin scrapings. Molecular tools offer the ability to rapidly diagnose dermatophytosis within 48 h. This study aimed to compare the results of a commercial real-time PCR (real-time PCR) assay DermaGenius®(DG) 2.0 complete multiplex kit with those of convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Dogo et al (2016) showed that the prevalence of Tinea capitis with regards to the age was lower for the age group from 5 to 10 years (42.6%) compared to the age group between 11 to 15 years (50%). Ndiaye et al (2022) reported the prevalence of Tinea capitis in prepubertal males (35.3%) was lower than that of females (56.7%) while the prevalence of Tinea capitis among the pubertal age between 11 to 15 years was lower in females (20%) compared to males (48.4%). Microsporum canis is commonly responsible for tinea capitis cases in South America, Australia, Africa and Western Europe (Table 1) while Trichophyton violaceum causes the majority of this superficial infection in South Asia and Eastern Europe (Gupta and Summerbell, 2000).…”
Section: Epidemiologymentioning
confidence: 90%
See 3 more Smart Citations
“…Dogo et al (2016) showed that the prevalence of Tinea capitis with regards to the age was lower for the age group from 5 to 10 years (42.6%) compared to the age group between 11 to 15 years (50%). Ndiaye et al (2022) reported the prevalence of Tinea capitis in prepubertal males (35.3%) was lower than that of females (56.7%) while the prevalence of Tinea capitis among the pubertal age between 11 to 15 years was lower in females (20%) compared to males (48.4%). Microsporum canis is commonly responsible for tinea capitis cases in South America, Australia, Africa and Western Europe (Table 1) while Trichophyton violaceum causes the majority of this superficial infection in South Asia and Eastern Europe (Gupta and Summerbell, 2000).…”
Section: Epidemiologymentioning
confidence: 90%
“…In all forms of Tinea capitis, the characteristic features include inflammation and partial hair loss. There is a correlation between T-lymphocyte activation, inflammatory responses and recovery (Ndiaye et al, 2022). Adesiji et al (2019) reported a case-control study to examine the etiological agents and predispose factors of tinea capitis from school pupils and observed that Tinea capitis is more common in children of age between 4 to 11 years.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…For limited sets of the most common species, a commercial non-culture, molecular assay, DermaGenius 2.0 multiplex real-time PCR kit (Pathonostics, Maastricht, The Netherlands) are available. This tool provides rapid detection of superficial fungal infections of nail, hair, and skin samples and readily differentiates species of Trichophyton , Microsporum and Epidermophyton in addition to Candida albicans ( Ndiaye et al, 2022 ). The kit lacks a probe for T. indotineae , a resistant and hypervirulent dermatophytes species ( Singh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%